Changes in cell surface and metabolism associated with strains of Listeria monocytogenes displaying different sensitivities to class IIa bacteriocins - Vadyvaloo, Viveka (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2003.